PKM workshop talking stick pada Guru SD Inpres Tidung II Kota Makassar - Nur Abidah Idrus; Nursiah B; Nurhaedah Nurhaedah (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of this Talking Stick learning model training program is to train teachers in applying various innovative approaches in the teaching and learning process and increase teachers' insights on the application of varied methods / approaches so as not to give birth to boredom in the teaching process both for teachers themselves and students as participants students. Makassar City has several elementary schools, one of which is the Tidung II Inpres Elementary School with a address at Jalan. Bonto daeng Ngirate No. 10 A Bonto Makkio, Tidung Village, Rappocini District, Makassar City South Sulwesi Provention. Date of Decree of establishment 1910-01-01 with ownership status of the central government with state status, accreditation B and NPSN: 40307522. SD Inpres Tidung II School principal Hasdawati, with 10 permanent teachers and 349 students consisting of 171 men and 179 women . The problems faced by teachers at Makassar's Tidung II Elementary School (Mitra) in the community partnership program are as follows: 1). Teachers still do not understand / know innovative approaches in the learning process.2). Teachers have not optimally applied varied learning so that the learning process is loaded with conventional approaches. Improve students' speaking skills through the Talking stick learning model. The main methods adopted in implementing the community partnership program (PKM) are as follows; the presentation time of the Talking stick learning model material, using the lecture and question and answer method. At the time of the training the application of the process skills approach to the method used was demonstration or practice. Outputs The training activities are (1) Participants have knowledge and add insight into the Talking stick learning model in teaching speaking skills (2) Participants can apply in a more innovative learning process that is the Talking stick learning model (3). Improve students' reading skills through the Talking stick learning model. Based on the results of this training activity, it can be shown that what is proposed in the formulation of the problem can be carried out properly and directed. From the results of these implementation activities get an answer that teachers in participating in this activity are very enthusiastic and the ability of teachers to apply active learning is very good. This valuable opportunity was not wasted even though it was realized that starting from the time and facilities and infrastructure was very limited, but with a strong enthusiasm and encouragement from the school principals, making this activity can take place successfully and was very useful and beneficial. The implementation of this activity was carried out at SD Inpres Tidung II Makassar City for 5 days. The results of the implementation of this activity are the participants have been able to understand and practice the Talking stick learning model as a form of active learning teaching. The conclusions of this training activity are (1) Participants are aware that the material provided is very motivating and diversity in teaching, (2) Participants who participate in the training are all teachers of SD Inpres Tidung II Makassar Municipality and honorary who are experienced enough in learning. And when the training took place they were very enthusiastic in following the training process. The results of this training greatly enrich the knowledge that can be used as provisions for the future.